Efficacy of celastrol-supplemented diet in overweight and obese dogs: a 24-week randomized controlled trial - Shin, Sang-Yoon; Cho, Woo-Jae; Yoon, Hun-Young; Lee, SooJung; Lee, Jeong-Ik; Kim, Mu-Young (Frontiers in Veterinary Science, 2026)
Obesity is an increasingly common health issue among companion animals, contributing to various disorders and reduced life expectancy. Traditional management strategies such as caloric restriction and physical activity show limited long-term success, highlighting the need for alternative options. Celastrol, a leptin-sensitizing agent derived from Tripterygium wilfordii, has shown potent anti-obesity effects in rodent models; however, its effects in dogs have not been studied. This study evaluated the efficacy and safety of celastrol-supplemented feeding in overweight and obese dogs. Seventeen client-owned dogs (BCS ≥ 6) were randomly assigned to receive either a celastrol-supplemented diet or an isocaloric control diet for 24 weeks. Clinical parameters, including body weight, serum leptin concentrations, and physical activity were assessed at regular intervals. Dogs in the celastrol group exhibited a significantly greater reduction in body weight (mean 8.7%) compared to the control group (mean 2.1%) (p = 0.003). Serum leptin concentrations also decreased more markedly in the celastrol group, although no significant group-by-time interaction was detected. No significant differences were found between groups in thoracic and abdominal girth, BCS, MCS, physical activity, or blood chemistry. Importantly, no adverse clinical events were observed, and blood chemistry remained within reference ranges, supporting systemic safety. These findings suggest that celastrol supplementation effectively promotes weight loss without evident safety concerns in overweight and obese dogs. The results provide preliminary in vivo evidence for celastrol’s applicability in veterinary medicine and support its potential as an adjunctive strategy for obesity management. Further studies with larger and more diverse populations are warranted to validate these results.